Micro-RNA Expression and Function in Lymphomas. (10th February 2011) - Sandhu, Sukhinder K.; Croce, Carlo M.; Garzon, Ramiro
Abstract : The recent discovery of microRNAs (miRNAs) has introduced a new layer of complexity to the process of gene regulation. MiRNAs are essential for cellular function, and their dysregulation often results in disease. Study of miRNA expression and function in animal models and human lymphomas has improved our knowledge of the pathogenesis of this heterogeneous disease. In this paper, we attempt to describe the expression of miRNAs and their function in lymphomas and discuss potential miRNA-based therapies in the diagnosis and treatment of lymphomas.